1965
DOI: 10.1063/1.1696441
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosonium Nitrate. Isolation at 79°—205°K and Infrared Spectra of the Polymorphic Compound

Abstract: Nitrosonium nitrate, NO+NO3−, a red solid, has been studied spectroscopically at temperatures ranging up to 205°K. Reproducible shifts of fundamental frequencies upon warming suggest two crystalline transformations between 79° and 205°K. The γ-, β-, and α-phase have been observed under nonequilibrium conditions in the following temperature ranges, respectively: 79°—185°, 167°—187°, 167°—205°K. The fundamental frequencies of the constituent ions in the γ, β, and α phase are: ν(NO)+: 2215, 2271, 2251 cm−1; ν3: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…2 is uptake of gaseous N 2 O 4 on the surface and its isomerization to surface asymmetric ONONO 2 . This isomerization is known to occur in solid matrices at low temperatures or high pressures, on ice and in solution, 101,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] (although one study 151 observed only the symmetric form of N 2 O 4 on ice films). Koel and coworkers [148][149][150]152 proposed that this isomerization occurs via the free O-H groups on amorphous ice, and it is possible that a similar process occurs in the thin films studied here.…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…2 is uptake of gaseous N 2 O 4 on the surface and its isomerization to surface asymmetric ONONO 2 . This isomerization is known to occur in solid matrices at low temperatures or high pressures, on ice and in solution, 101,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] (although one study 151 observed only the symmetric form of N 2 O 4 on ice films). Koel and coworkers [148][149][150]152 proposed that this isomerization occurs via the free O-H groups on amorphous ice, and it is possible that a similar process occurs in the thin films studied here.…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…A huge number of reports have already appeared on N 2 O 4 species, and we are not inclined to give a comprehensive overview. N 2 O 4 derivatives were investigated in the liquid [6][7][8] and solid state; [9][10][11][12] in liquid rare gases; [13,14] organic solvents; [6,15,16] in various solid matrices such as Ne, [17] Ar, [18][19][20][21] N 2 [22] and O 2 ; [19,20] and adsorbed on amorphous and crystalline water-ice films. [23,24] These studies have shown that two NO 2 radicals in principle may combine to various N 2 O 4 species.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists those species that may be envisioned and includes the ionic nitrosonium nitrate, NO + NO 3 À . [15,24,[43][44][45][46][47] Those species that are proposed to be involved in the oxidation of NO by O 2 are marked by a tick. Although many of these species may exist only as short-lived intermediates in the gas phase, if they are prevented from reacting to form more stable species, as for example, by isolation in rare-gas matrices, they can in principle be detected and characterised by using spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations